Application of reliable cost-effective strategy for analysis of mycotoxins in corn-based foods with HPLC-FLD after multi-toxin immunoaffinity clean-up - Stojanovska Dimzoska, Biljana; Hajrulai Musliu, Zehra; Uzunov, Risto; Angeleska, Aleksandra; Blagoevska, Katerina; Crceva Nikolovska, Radmila; Ilievska, Gordana; Dimitrieska Stojkovic, Elizabeta (Society of Chemists and Technologists of Macedonia, 2022)
A different, reliable, and cost-effective strategy for the analysis of aflatoxins, ochratoxin A, and zearalenone in corn-based foods was proposed, including one multi-toxin immunoaffinity column (IAC) sample preparation and three different high-performance liquid chromatography fluorescence detection methods. The analytical procedures were tested and verified, keeping in mind their occurrence at trace levels in corn-based foods. With the validation of the proposed multi-toxin IAC methodology and comparison of the performance characteristics with methods using a single-toxin IAC, we confirmed the reliability of the multi-toxin IAC procedure versus the single-toxin IAC. The methods were validated by revealing satisfactory performance characteristics; for example, the obtained values of limit of detection were significantly lower than the maximum limits for all mycotoxins of concern. In addition, the recovery values were between 70.9 % and 106.1 % for all mycotoxins of interest, with precision values lower than 10.5 %.
Keywords: mycotoxins; multi-toxin IAC; HPLC-FLD;validation